2021
DOI: 10.1038/s41467-021-23404-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of social distancing policies on mobility and COVID-19 case growth in the US

Abstract: Social distancing remains an important strategy to combat the COVID-19 pandemic in the United States. However, the impacts of specific state-level policies on mobility and subsequent COVID-19 case trajectories have not been completely quantified. Using anonymized and aggregated mobility data from opted-in Google users, we found that state-level emergency declarations resulted in a 9.9% reduction in time spent away from places of residence. Implementation of one or more social distancing policies resulted in an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 19 publications
(30 reference statements)
9
116
3
Order By: Relevance
“…Mobility decreased rapidly in March in concert with early transmission control policies and the statewide stay-at-home order, and mobility increased as social distancing policies were relaxed. Consistent with our findings, others have found that US population mobility was reactive to policy during March: greater perceived disease prevalence and governmental stay-at-home orders resulted in less mobility and social interaction (35)(36)(37). However, in Colorado, lifting stay-at-home orders and concurrent increases in mobility do not appear to have led to increased transmission, indicating the limitations in using mobility data to predict transmission.…”
Section: Discussionsupporting
confidence: 86%
“…Mobility decreased rapidly in March in concert with early transmission control policies and the statewide stay-at-home order, and mobility increased as social distancing policies were relaxed. Consistent with our findings, others have found that US population mobility was reactive to policy during March: greater perceived disease prevalence and governmental stay-at-home orders resulted in less mobility and social interaction (35)(36)(37). However, in Colorado, lifting stay-at-home orders and concurrent increases in mobility do not appear to have led to increased transmission, indicating the limitations in using mobility data to predict transmission.…”
Section: Discussionsupporting
confidence: 86%
“… Farboodi et al, 2021 , Nouvellet et al, 2021 , Bartscher et al, 2020 , VoPham et al, 2020 , Wellenius et al, 2021 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…People come into regular contact with living microorganisms when they touch these surfaces with their bare hands. Contaminated hands thus become a vector that transmits the bacteria or virus from a frequently touched surface to a person’s mucosal areas through face touching [ 16 , 17 ]. Because smartphone surfaces can be pathogen carriers, people must abandon the habit of smartphone touching paired with face touching to break the transmission chain of infectious disease.…”
Section: Discussionmentioning
confidence: 99%